2021
DOI: 10.18280/ria.350401
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Ovarian Cancer Types from CT Images Using Deep Semi-Supervised Generative Learning and Convolutional Neural Network

Abstract: The classification of ovarian cancer types is a very challenging process for physicians' eyes. To solve this problem, this article proposes a new deep learner, which classifies ovarian cancer types from Computerized Tomography (CT) images. Firstly, a Deep Convolutional Neural Network (DCNN) model depending on AlexNet is proposed to categorize ovarian cancer from CT images. But its efficiency is not satisfactorily high. So, DCNN is built based on the fusion of AlexNet, VGG, and GoogLeNet. The fusion is carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the proposed work by Goodfellow et al [ 10 ], an adversarial net framework was suggested that loosely resembles a minimax two-player game. Nagarajan et al [ 11 ] and Zhao et al [ 12 ], in their research work, provided three approaches that were used to classify ovarian cancer types using CT images. The first approach used a deep convolutional neural network (DCNN) based on AlexNet, which did not provide satisfactory results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the proposed work by Goodfellow et al [ 10 ], an adversarial net framework was suggested that loosely resembles a minimax two-player game. Nagarajan et al [ 11 ] and Zhao et al [ 12 ], in their research work, provided three approaches that were used to classify ovarian cancer types using CT images. The first approach used a deep convolutional neural network (DCNN) based on AlexNet, which did not provide satisfactory results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al. [11], in their research work, provide three approaches that are used to classify ovarian cancer types using CT images. The first approach uses a deep convolutional neural network (DCNN) based on AlexNet which does not provide satisfactory results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nagarajan and Tajunisha [16] talked about the sonographic characteristics of different ovarian cystic masses that can be discovered inside or outside the ovary. Ovarian cysts typically come in seven different forms.…”
Section: Related Workmentioning
confidence: 99%
“…The main source of evidence for the efficiency of the suggested strategy was our collection of images of ovarian tumors. As there isn't a publicly accessible liver image dataset, one was used instead to compare with current medical picture segmentation techniques [16]. Zhejiang University's School of Medicine's Affiliated Women's Hospital offered an ovarian tumor dataset used in this work, which includes 196 Ultrasound Images (UI) in total, as shown in Figure 2 some examples from images.…”
Section: Datasetsmentioning
confidence: 99%